Unlocking the Power of Digitalization: How Technology Shapes Employee Engagement and Organizational Performance - Izzatilah, Nuri; Manafe, Leonard Adrie; Rahardjo, Kusuma Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the extent to which digital measures affect employee engagement and productivity at PT. Bogajaya Megah Abadi. Using a phenomenological design, the researcher explores the personal narratives that emerge as staff adapt to new devices. Data was obtained through in-depth interviews and guided group discussions, involving six employees from various levels. Preliminary findings indicate that modern technology applications accelerate communication flows and make team collaboration feel more seamless. However, some individuals expressed feelings of isolation due to a significant reduction in face-to-face meetings. From a management perspective, digitalisation has successfully reduced process times, lowered operational costs, and improved service quality. The biggest challenge remains during the transition period, where training and new habits must be established. To bridge this gap, the study recommends that companies schedule regular training sessions and encourage social activities in the office. Researchers also encourage further study, perhaps by comparing these findings with other companies or attributing the specific effects of one technology platform to individual and team performance.